What Does the 'Smart City' Construct Not Yet Contain? - Adriana Carolina BULZ; Eliza Cristina BULZ; Nicolae BULZ (Smart Cities and Regional Development Journal)
Adriana-Carolina Bulz discusses contemporary humanistic limitations, paradoxes, false challenges and perspectives within a 'Smart City', while focusing on Don DeLilloâ€™s novel Cosmopolis (2003). Eliza Bulz expands on financial drift to learn from previous mistakes (by way of the 2008-2013 global financial crisis, and more versus the estate boom trick), while Nicolae Bulz starts from the concept of "Knowledge Society" and works toward "Consciousness Society" alongside the 'Smart City' construct.